Community contacts and participation of teachers in four towns in Zambales - Firme, Tito F. (Education quarterly.)
This study is a survey of the out-of-school life of teachers in which they generally come in contact with the community in three major areas: professional services, citizenship activities, and leisure time pursuits. In this activities, teachers have to adjust themselves to the level of community norms and expectations so as to be able to establish appropriate relations between the school and the community.